Some ocular symptoms and sensations experienced by long term users of mobile phones - Balik, HH; Turgut-Balik, D; Balikci, K; Özcan, IC (Editions Scientifiques Medicales Elsevier, 2005)
In this study, a survey was conducted to investigate the possible effects of long, term usage of mobile phone (MP) on eyes. The studied symptoms are blurring of vision, redness on the eyes, vision disturbance, secretion of the eyes, inflammation in the eyes and lacrimation of the eyes. There is no effect on redness on the eyes and vision disturbance, but some statistical evidences are found that MP may cause blurring of vision, secretion of the eyes, inflammation in the eyes and lacrimation of the eyes. These results suggest an awareness of the symptoms and sensations. (C) 2004 Elsevier SAS. All rights reserved.
Keywords: eye; ocular symptoms; mobile phone; long term use; microwave